GAPS IN MANAGING BLENDED LEARNING PROCESSES IN BORDER AREA SCHOOLS: EVIDENCE FROM BENGKAYANG, INDONESIA - Sadewo, Yosua Damas; Purnasari, Pebria Dheni; Saputro, Totok Victor Didik; Silvester, Silvester; Yimer, Nurselam Hassen (TEACHING : Jurnal Inovasi Keguruan dan Ilmu Pendidikan, 2026)
ABSTRACT Educational disparities between urban and border areas remain a critical issue within Indonesia’s education system. One manifestation of this disparity is the uneven management of blended learning-based instructional processes. This study aims to examine the gaps in managing blended learning processes in border area schools, using Bengkayang Regency as the context of analysis. This study employs a literature review approach by analyzing national and international journal articles, government reports, and relevant educational statistical data. Data were analyzed using thematic analysis to identify patterns, challenges, and characteristics related to the management of blended learning in border areas. The findings indicate that the implementation of blended learning in border areas faces multiple constraints, including limited technological infrastructure, low teacher readiness, insufficient institutional support, and sociocultural conditions that are not yet conducive to digital learning. These findings suggest that the success of blended learning is not solely determined by technological availability, but also by the quality of contextual and realistic instructional management. This study is expected to contribute theoretically and practically to the development of blended learning management in border area schools. ABSTRAK Kesenjangan pendidikan antara daerah perkotaan dan perbatasan tetap menjadi isu kritis dalam sistem pendidikan Indonesia. Salah satu manifestasi kesenjangan ini adalah pengelolaan proses pembelajaran campuran yang tidak merata. Studi ini bertujuan untuk meneliti kesenjangan dalam pengelolaan proses pembelajaran bauran di sekolah-sekolah daerah perbatasan, dengan menggunakan Kabupaten Bengkayang sebagai konteks analisis. Studi ini menggunakan pendekatan tinjauan pustaka dengan menganalisis artikel jurnal nasional dan internasional, laporan pemerintah, dan data statistik pendidikan yang relevan. Data dianalisis menggunakan analisis tematik untuk mengidentifikasi pola, tantangan, dan karakteristik yang berkaitan dengan pengelolaan pembelajaran bauran di daerah perbatasan. Temuan menunjukkan bahwa implementasi pembelajaran campuran di daerah perbatasan menghadapi berbagai kendala, termasuk infrastruktur teknologi yang terbatas, kesiapan guru yang rendah, dukungan kelembagaan yang tidak memadai, dan kondisi sosial budaya yang belum kondusif untuk pembelajaran digital. Temuan ini menunjukkan bahwa keberhasilan pembelajaran bauran tidak hanya ditentukan oleh ketersediaan teknologi, tetapi juga oleh kualitas pengelolaan pembelajaran yang kontekstual dan realistis. Studi ini diharapkan dapat memberikan kontribusi secara teoritis dan praktis terhadap pengembangan pengelolaan pembelajaran bauran di sekolah-sekolah daerah perbatasan.